Habiter l’exil : Retablo hispánico, Mexique, 1946 - Salomé Foehn (Cahiers de Civilisation Espagnole Contemporaine)
In 1946, Spanish Republican intellectuals in exile published a miscellanea of texts, entitled Retablo hispánico, with the ephemeral, Mexico-founded publishing house, « Clavileño ». Despite the important critical bibliography of cultural Spanish Republican exile, little if no attention has been paid to this unique product. In this article I will analyse the contributions of three important philosophers of the generation known as « generación de la República » or « primera generación del exilio de 1939 » : Joaquín Xirau, Juan David García Bacca, José M. Gallegos Rocafull and José Gaos. To do so, I will propose a theoretical framework based on recent works in two complementary fields : historiography of philosophy and Spanish exile studies. Indeed, as unhoused « pilgrims », they present an « altarpiece » which is also meant as the « justification » of exile as the redeeming perspective of a much darker Spain, that of the Black Legend. I will first look at several philosophical reflections. Some are classical, wherein the mother tongue is considered as « home », and exile as « non-lieu ». For this generation of exiles, to inhabit is a philosophical « gesture » (Benoît Goetz), a harmonic and contrapuntal « way of being » (Edward Said). The authors I focus on validate in philosophical terms what is organically constitutive of the Spain they lost in 1939 : the Castilian idiom. There is a twofold benefit to Castillian in their works : it is acknowledged in philosophical terms for the first time in the history of philosophy, and is materialized through the extensive literary production – yet to come. The Retablo is, undoubtedly, a production no less than exemplary. Originally a work written collectively which the Republican government in exile sponsored, it was offered as a gift to General Lázaro Cárdenas. It scarcely reached the general audience – only selective circles of experts accessed it.